2022
DOI: 10.1111/jpn.13774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxidized soybean oil on the performance of sows and jejunum health of suckling piglets

Abstract: Oils provide a considerable amount of energy to the swine diet, but they are prone to lipid oxidation if not properly preserved. Consumption of oxidized oils can adversely affect the animal organism and even the offspring. This study investigated the impact of oxidized soybean oil in the diets of sows from 107 days gestation to 21 days of lactation on the performance of sows and jejunum health of suckling piglets.Sixteen sows were randomly allocated into two groups: one group (n = 8) was fed with the fresh soy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Some studies have reported that dietary oxidized fish oil decreases average daily gain, significantly increases F/G, decreases the apparent digestibility levels of nutrients from dry matter and ether extract, and increases the diarrhea indices of weaned piglets [42]. However, no effects of oxidized soybean oil on the growth performance levels of piglets are found in our study, similar to the results of Gao et al [43], who found that dietary supplementation with oxidized soybean oil does not affect the performance levels of sows [43]. This suggests that the weaned piglet body itself may have a certain regulatory role to cope with the stress caused by low oxidation degree of oil.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have reported that dietary oxidized fish oil decreases average daily gain, significantly increases F/G, decreases the apparent digestibility levels of nutrients from dry matter and ether extract, and increases the diarrhea indices of weaned piglets [42]. However, no effects of oxidized soybean oil on the growth performance levels of piglets are found in our study, similar to the results of Gao et al [43], who found that dietary supplementation with oxidized soybean oil does not affect the performance levels of sows [43]. This suggests that the weaned piglet body itself may have a certain regulatory role to cope with the stress caused by low oxidation degree of oil.…”
Section: Discussionsupporting
confidence: 90%
“…can be produced by activating NF-κB at the molecular level. , Therefore, OSO may damage the liver by affecting oxidative stress and inflammatory immune response. We previously showed that adding peroxide oil to sows’ diets can cause intestinal tissue inflammation in offspring . Another study showed similar results that feeding oxidized rapeseed oil resulted in the activation of oxidative stress factor nuclear factor erythroid-derived 2-like 2 (Nrf2) and the activation of inflammatory pathway NF-κB .…”
Section: Discussionmentioning
confidence: 74%
“…We previously showed that adding peroxide oil to sows' diets can cause intestinal tissue inflammation in offspring. 23 Another study showed similar results that feeding oxidized rapeseed oil resulted in the activation of oxidative stress factor nuclear factor erythroidderived 2-like 2 (Nrf2) and the activation of inflammatory pathway NF-κB. 42 In addition, feeding oxidized fish oil exacerbated liver inflammation, resulting in increased proinflammatory cytokines, while anti-inflammatory cytokines (IL-10) are lowered.…”
Section: ■ Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our previous studies have shown that maternal exposure to OSO damages the placental, 29 the offspring's liver, 30 kidney, 31 and intestine. 32,33 Hence, it is especially significant to seek out a way to mitigate the damage of an OSO to both maternal and offspring.…”
Section: ■ Introductionmentioning
confidence: 99%